Rate of atrial fibrillation and flutter induced tachycardiomyopathy in a cohort of hospitalized patients with heart failure and detection of indicators for improved diagnosis - Ermert, Lynn; Kreimer, Fabienne; Quast, Daniel R.; Pflaumbaum, Andreas; Mügge, Andreas; Gotzmann, Michael (Frontiers in Cardiovascular Medicine, 2023)
Background: Atrial fibrillation (AF) and atrial flutter (AFL) induced tachycardiomyopathy (TCM) has been known to cause reversible heart failure (HF) for many years. However, the prevalence of the disease is unknown, and diagnosis is challenging. Therefore, the aim of the present study was 1) to assess the rate of AF/AFL induced TCM and 2) to identify indicators for diagnosis. Methods: Consecutively, all patients with a diagnosis of HF who were hospitalized in our department within 12 months were reviewed. For the main analysis, all patients with HF with reduced ejection fraction (HFrEF) and AF or AFL were included. AF/AFL induced TCM was diagnosed when there was at least a 10% improvement in left ventricular ejection fraction under rhythm or rate control within three months. Patients with HFrEF with AF/AFL but without TCM served as control group. Results: 480 patients were included. AF/AFL induced TCM occurred in 26 patients (5.4%) and HFrEF with AF/AFL in 53 patients (11%). Independent indicators of AF/AFL induced TCM were age <79 years (Odds ratio 5.887, confidence interval [CI] 1.999–17.339, p<0.001), NT-pro-BNP <5419 pg/mL (Odds ratio 2.327, CI 1.141–4.746, p=0.004), and a resting heart rate >112 bpm (Odds ratio 2.503, CI 1.288–4.864, p=0.001). Conclusion: Approximately 5% of all patients hospitalized for HF suffer from AF/AFL induced TCM. Improved discrimination of AF/AFL induced TCM to HFrEF with AF/AFL is possible considering age, NT-pro-BNP level, and resting heart rate > 112 beats/minute. Based on these parameters, an earlier diagnosis and improved therapy might be possible.